The Influence of Reciprocal Teaching on Reading Ability Achievement - Wargadinata, Fahmi Rido; Hanafi, Hanafi; Oktarini, Widya (Indonesian Journal Publisher, 2023)
The importance of reading comprehension is rising in the field of education. For students to read proficiently, instruction and practise are necessary. Making meaning of a text is a component of reading comprehension. Consequently, rather of focusing on understanding a particular phrase or word, readers should aim to gain a comprehensive knowledge of the material presented in the book. One of method that could improve students reading ability is reciprocal method. this study aims to investigate how reciprocal teaching can enhance students' reading comprehension of descriptive texts. A quantitative method was used to summarize the data that was obtained from the outcome. Students from SMP 1 Muhammadiyah Jember are the participant for this research. 8 grade B as the experimental class while 8 grade A as control class. These students have studied descriptive text. The class 8 B was experimental group which was taught reading text using reciprocal method. The class 8 A was control group that was taugh reading only based on the text book. The data that have been collected then analyzed using spss to find if there is any significat effect in using reciprocal method in students reading comprehension.the result of the independent sample t-test on SPSS program, The value of sig (2-tailed) was 0.001 and it was less than 0.05. It could be revealed that there was a significant difference between the experimental group and the control group after. In other words, there was a significant effect of using reciprocal on the eighth-grade students’ reading score at SMP 1 Muhammadiyah Jember.